Multisectoral approach and WHO ‘Bestbuys’ in Nigeria’s nutrition and physical activity policies (2020)
Unhealthy diet and physical inactivity are modifiable risk factors for non-communicable diseases. Policies formulated in line with international guidelines are required for the implementation of population-level interventions to reduce the risks. This study describes the utilization of multisectoral approach (MSA) for the formulation of nutrition and physical activity policies and the extent to which they align with the WHO ‘Best Buy Interventions’. The research utilized a descriptive case study design and the theoretical model guiding the study was the Walt and Gilson framework for policy analysis. Data were obtained through the interview of 44 key informants using pre-tested guides and document review of 17 policies and articles obtained from government institutions or through the search of electronic databases. Data were integrated and analysed using thematic analysis. Between 2000 and 2016, Nigeria had formulated 10 nutrition-related policies and 5 guidelines with actions to promote physical activity. Only three nutrition and two physical activity policies adopted a high level of MSA. In line with the WHO best buy interventions, educational interventions for the general population are proposed to reduce sugar and salt intake and replace transfat with polyunsaturated fats but there are no legal regulatory acts to support these actions. Policy documents with actions to reduce physical inactivity do not include the WHO best buys. The country should adopt a wider range of actors to formulate and review policies, integrate all the WHO best buy interventions and develop effective legislation to regulate the salt and sugar content of processed foods.